The Hsp90 Cochaperones Cpr6, Cpr7, and Cns1 Interact with the Intact Ribosome - Tenge, Victoria R. (Eukaryot Cell, 2014)
The abundant molecular chaperone Hsp90 is essential for the folding and stabilization of hundreds of distinct client proteins. Hsp90 is assisted by multiple cochaperones that modulate Hsp90's ATPase activity and/or promote client interaction, but the in vivo functions of many of these cochaperones are largely unknown. We found that Cpr6, Cpr7, and Cns1 interact with the intact ribosome and that Saccharomyces cerevisiae lacking CPR7 or containing mutations in CNS1 exhibited sensitivity to the translation inhibitor hygromycin. Cpr6 contains a peptidyl-prolyl isomerase (PPIase) domain and a tetratricopeptide repeat (TPR) domain flanked by charged regions. Truncation or alteration of basic residues near the carboxy terminus of Cpr6 disrupted ribosome interaction. Cns1 contains an amino-terminal TPR domain and a poorly characterized carboxy-terminal domain. The isolated carboxy-terminal domain was able to interact with the ribosome. Although loss of CPR6 does not cause noticeable growth defects, overexpression of CPR6 results in enhanced growth defects in cells expressing the temperature-sensitive cns1-G90D mutation (the G-to-D change at position 90 encoded by cns1). Cpr6 mutants that exhibit reduced ribosome interaction failed to cause growth defects, indicating that ribosome interaction is required for in vivo functions of Cpr6. Together, these results represent a novel link between the Hsp90 molecular-chaperone machine and protein synthesis.